Uji Aktivitas Sitotoksik Ekstrak Kulit Bawang Putih (Allium satovum L.) Dengan Metode BSLT (Brine Shrimp Lethality Test) - Hesti Marliza; Yunisa Friscia Yusri; Henny Rachdiati (Jurnal Ilmiah Kedokteran dan Kesehatan, 2022)
Garlic (Allium sativum L.) stores many benefits as traditional medicines that have long been known to overcome and prevent various diseases such as antimicrobials, anticancers, antioxidants and antidiabetics but the potential of garlic skin research has not been found as an anticancer by using the BSLT (Brine shrimp lethality test) method as a preliminary test. This study was conducted to find out the toxicity of garlic skin extract (Allium sativum L.) using the BSLT extract method made by maceration using methanol solvent. Toxicity tests are performed using the larvae of the 48-hour-old Artemia saline Leach shrimp. The toxic effects of the extract are identified with a percentage of shrimp larva mortality using probit analysis (LC50). The results showed that garlic skin extract contains alkaloid compounds, flavonoids, phenolics, and triterpenoids. Toxic extracts are characterized by LC50 values <1000μg/ml. and the results of the toxicity test of garlic skin extract with methanol solvent have an LC50 value of 44.18μg / ml with toxic category. Keywords: Garlic Tuber skin ((Allium sativum L.), Brine Shrimp Lethality Test, The results showed that garlic skin extract contains alkaloid compounds, flavonoids, phenolics, and triterpenoids. Toxic extracts are characterized by LC50 values <1000μg/ml. and the results of the toxicity test of garlic skin extract with methanol solvent have an LC50 value of 44.18μg / ml with toxic category.